The method of shariah-compliance gold investment : conceptual research / Muhammad Arif Azhan Abdul Malik - Abdul Malik, Muhammad Arif Azhan (Universiti Teknologi MARA, Selangor, Puncak Alam Campus, 2018)
Gold investment is one of the tremendous investment because investing in gold grant the society more than just economic in terms of monetary worth, people are more intense on possessing gold as it is treasured as a display and storage of culture and greed. In Malaysia there are Islamic banks that carry out shariah-compliant gold investments. This study examines the shariah-compliant gold investment in Islamic concepts. Data and information obtained through documentation method are then analyzed using inductive and deductive methods with gold transaction theory according to an Islamic economic perspective. The study wil elaborate about the elements that needed to be comply in the investment for acquiring the name of shariah-compliance investment. The result shows that almost all implementation of Islamic banking gold investment products are in compliance with shariah. The methods that are been use in the gold investment the gold transaction (al-sarf) and debt (qard).